Vitamin D deficiency and exogenous vitamin D excess similarly increase diffuse atherosclerotic calcification in apolipoprotein E knockout mice. - Timothy Ellam; Abdul Hameed; Risat ul Haque; Munitta Muthana; Martin Wilkie; Sheila E Francis; Timothy J A Chico (PLoS ONE)
Background Observational data associate lower levels of serum vitamin D with coronary artery calcification, cardiovascular events and mortality. However, there is little interventional evidence demonstrating that moderate vitamin D deficiency plays a causative role in cardiovascular disease. This study examined the cardiovascular effects of dietary vitamin D deficiency and of vitamin D receptor agonist (paricalcitol) administration in apolipoprotein E knockout mice. Methods Mice were fed atherogenic diets with normal vitamin D content (1.5 IU/kg) or without vitamin D. Paricalcitol, or matched vehicle, was administered 3× weekly by intraperitoneal injection. Following 20 weeks of these interventions cardiovascular phenotype was characterized by histological assessment of aortic sinus atheroma, soluble markers, blood pressure and echocardiography. To place the cardiovascular assessments in the context of intervention effects on bone, structural changes at the tibia were assessed by microtomography. Results Vitamin D deficient diet induced significant reductions in plasma vitamin D (p<0.001), trabecular bone volume (p<0.01) and bone mineral density (p<0.005). These changes were accompanied by an increase in calcification density (number of calcifications per mm(2)) of von Kossa-stained aortic sinus atheroma (461 versus 200, p<0.01). Paricalcitol administration suppressed parathyroid hormone (p<0.001), elevated plasma calcium phosphate product (p<0.005) and induced an increase in calcification density (472 versus 200, p<0.005) similar to that seen with vitamin D deficiency. Atheroma burden, blood pressure, metabolic profile and measures of left ventricular hypertrophy were unaffected by the interventions. Conclusion Vitamin D deficiency, as well as excess, increases atherosclerotic calcification. This phenotype is induced before other measures of cardiovascular pathology associated clinically with vitamin D deficiency. Thus, maintenance of an optimal range of vitamin D signalling may be important for prevention of atherosclerotic calcification.